Has the Opioid Crisis Affected Student Learning? A National Analysis of Growth Rates. Issue 1 (September 2022) - Drescher, Jessica; Steyer, Lily; Townley-Flores, Carrie; Humphreys, Keith
The potential spillover effects of the United States' opioid epidemic on children's educational outcomes have received surprisingly little attention from researchers. Accordingly, this study leverages national datasets of county-level opioid prescription rates and public school students' third- to eighth-grade academic achievement to provide the first analysis of associations between community opioid prevalence and children's learning rates. We find that students in counties with higher community opioid presence learn more slowly than peers in counties with low community opioid presence, both in aggregate and across different racial, ethnic, and socioeconomic groups of students. Moreover, within states we observe a small significant negative association between community opioid presence and student learning rates. This association is similar in rural and nonrural communities. These findings underscore the urgency of conceptualizing the opioid epidemic as a community-level crisis, with potentially long-lasting implications for children's future educational attainment and life outcomes.